SENECA study: staging endometrial cancer based on molecular classification - Chacon, Enrique; Boria, Felix; Lyer, R Rajagopalan; Fanfani, Francesco; Malzoni, Mario; Bretová, Petra; Luzarraga Aznar, Ana; Fruscio, Robert; Jedryka, Marcin A; Tóth, Richard; Perrone, Anna Myriam; Kakkos, Athanasios; et al. (International journal of gynecological cancer, 2024)
OBJECTIVE: Management of endometrial cancer is advancing, with accurate staging crucial for guiding treatment decisions. Understanding sentinel lymph node (SLN) involvement rates across molecular subgroups is essential. To evaluate SLN involvement in early-stage (International Federation of Gynecology and Obstetrics 2009 I-II) endometrial cancer, considering molecular subtypes and new European Society of Gynaecological Oncology (ESGO) risk classification. METHODS: The SENECA study retrospectively reviewed data from 2139 women with stage I-II endometrial cancer across 66 centers in 16 countries. Patients underwent surgery with SLN assessment following ESGO guidelines between January 2021 and December 2022. Molecular analysis was performed on pre-operative biopsies or hysterectomy specimens. RESULTS: Among the 2139 patients, the molecular subgroups were as follows: 272 (12.7%) p53 abnormal (p53abn, 1191 (55.7%) non-specific molecular profile (NSMP), 581 (27.2%) mismatch repair deficient (MMRd), 95 (4.4%) POLE mutated (POLE-mut). Tracer diffusion was detected in, at least one side, in 97.2% of the cases; with a bilateral diffusion observed in 82.7% of the cases. By ultrastaging (90.7% of the cases) or one-step nucleic acid amplification (198 (9.3%) of the cases), 205 patients were identified with affected sentinel lymph nodes, representing 9.6% of the sample. Of these, 139 (67.8%) had low-volume metastases (including micrometastases, 42.9%; and isolated tumor cells, 24.9%) while 66 (32.2%) had macrometastases. Significant differences in SLN involvement were observed between molecular subtypes, with p53abn and MMRd groups having the highest rates (12.50% and 12.40%, respectively) compared with NSMP (7.80%) and POLE-mut (6.30%), (p=0.004); (p53abn, OR=1.69 (95% CI 1.11 to 2.56), p=0.014; MMRd, OR=1.67 (95% CI 1.21 to 2.31), p=0.002). Differences were also noted among ESGO risk groups (2.84% for low-risk patients, 6.62% for intermediate-risk patients, 21.63% for high-intermediate risk patients, and 22.51% for high-risk patients; p<0.001). CONCLUSIONS: Our study reveals significant differences in SLN involvement among patients with early-stage endometrial cancer based on molecular subtypes. This underscores the importance of considering molecular characteristics for accurate staging and optimal management decisions.
Keywords: Sentinel Lymph Node; Humans; lidé středního věku; Female; Aged; dospělí; Endometrial Neoplasms; senioři; lidé; Lymphatic Metastasis; lymfatické metastázy; biopsie sentinelové lymfatické uzliny; Adult; staging nádorů; ženské pohlaví; Sentinel Lymph Node Biopsy; Middle Aged; Retrospective Studies; Aged, 80 and over; senioři nad 80 let; nádory endometria; retrospektivní studie; sentinelová uzlina; Neoplasm Staging